Kualitas Hidup Pasien Gagal Ginjal Kronis yang Menjalani Hemodialisa - Rustendi, Teten; Murtiningsih, Murtiningsih; Inayah, Iin (Mando Care Jurnal, 2022)
Chronic renal failure is a progressive and irreversible renal function disorder in which the body's ability fails to maintain metabolism and fluid and electrolyte balance, causing uremia (retention of urea and other nitrogenous wastes in the blood). In Indonesia, the increase in patients with this disease has reached 20%. The data and information center of the Indonesian Hospital Association (PDPERSI) states that the number of patients with chronic kidney failure is estimated at around 50 people per one million population. Hemodialysis is very important for patients with chronic kidney failure because hemodialysis is one of the measures that can prevent death. However, hemodialysis cannot cure or restore kidney disease because it is unable to compensate for the loss of metabolic activity of kidney or endocrine diseases carried out by the kidneys and the impact of kidney failure and therapy on the patient's quality of life. Objective to determine the quality of life of chronic kidney failure patients undergoing hemodialysis. Using a literature review study method from scientific journals with keyword guidance. Scientific journals that were selected were 6 journals, each journal representing one quality of life of chronic kidney failure patients undergoing hemodialysis. The quality of life of patients with chronic kidney failure are mostly in the good or high category with many factors affecting the quality of life of patients with chronic failure who are undergoing hemodialysis. Based on the analysis that has been carried out, it shows that the quality of life of patients with chronic failure at the good or high category level the biggest influencing factors are family support and self-efficacy.